Food security, poverty, and economic policy in the Middle East and North Africa - Lofgren, Hans; Richards, Alan (International Food Policy Research Institute, 2003)
In MENA, household food insecurity, which is closely related to poverty and undernourishment, is most severe in rural areas and concentrated within Iraq, Sudan, and Yemen. 25% of the MENA population may be poor and 7% undernourished. The key to increased national and household-level food security is pro-poor growth, driven by export-oriented, labor-intensive sectors. Agricultural sector policies should be subordinate to the pro-poor growth goal and not to the goal of food self-sufficiency. Such a strategy requires conflict resolution; macroeconomic stability; physical and human capital accumulation; reliance on markets and the private sector, and diffusion of ecologically friendly farming practices.